Early Detection, Treatment, & Prevention Program In Indonesia - REPUBLIK INDONESIA, KEMENTRIAN KESEHATA (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43600135/Early-Detection-Treatment-Prevention-Program-In-Indonesia